The picric acid: an ancient ally of analytical chemistry that is still relevant today - Vargas Mamani, Juan Jose (2021)
Picric acid is a molecule that was born as a dye, made its foray as a secondary explosive and was used during World War I and II. Today, it is employed in phytochemical and biochemical identification techniques. In this article I try to highlight its usefulness in the past and present, detaching it from its crucial warlike past to highlight its use in times of peace.